Artificial intelligence based watermarking in hybrid DDS domain for security of colour images. (16th December 2020) - Sharma, Sourabh; Sharma, Harish; Sharma, Janki Ballabh
A colour image watermarking based on artificial bee colony (ABC) optimisation in hybrid DDS (DWT-DCT-SVD) transform domain using arnold transform is performed. The host/cover colour image is transformed into the YCbCr colour channel and applies a discrete wavelet transform (DWT) to decompose into 4 sub-bands. Then all sub-bands undergo discrete cosine transform (DCT) individually. After that singular values of each sub-bands are calculated using singular value decomposition (SVD). The original watermark is first encrypted by arnold transform and divided into four different parts of equal dimension to embed in each sub-band of the host/cover image using an optimised scaling factor. Robustness is analysed by the experimental analysis through different image threatening attacks. To confirm the resisting capacity of the proposed scheme the NC results are compared with other watermarking schemes present in the literature.